The impact of a training program to develop your stamina in some physical and functional capacities of handball players - Kareem, Nimaat (Journal of Physical Education, 2015)
The importance of research in the use of this proposed program through which develops your stamina to the effectiveness of handball, and is the research problem in the lack of attention to side endurance, it did not take the role and size of the real in the training process within the stomach curriculum by trainers and various Bosalebha and according to proper scientific method , so it felt a researcher studying this problem. The research aims to develop a training program to develop your stamina in the development of some of the physical and functional capacity and performance of diving grab on the two men to the category of applicants in the game of wrestling. The researcher used the experimental method by comparing the experimental group with the control group. And that the most important conclusions that the researcher that your stamina exercises helped to develop the physical and functional capabilities of the players who trained them, and their superiority on the development of players who trained without them. And that the most important recommendations made by the researcher recommends omitted need your stamina exercises are a way similar technical performance including muscle force training skills under study